In vitro antioxidant, antimicrobial and phytochemical properties of wild banana [Ensete gilletii (E. A. J. DE Wildman)] seeds extract - Afolayan, Michael; Abubakar, Salisu; Adedayo, Adebiyi; Doyinsola, Idowu; Adebisi, Fagbohun (International Journal of Advanced Chemistry, 2014)
The proximate composition and phytochemical contents of wild banana seeds was examined. The seeds were also powdered and extracted with hexane, ethyl acetate and ethanol and each extract tested for its antimicrobial, antioxidant and phytochemical properties. The proximate analysis of the raw seeds showed that it contained carbohydrates – 68.41%, proteins – 11.16%, crude fibre – 1.1%, lipids – 6.27%, ash – 3.20% and moisture – 9.86% while its phytochemical investigation revealed the presence of carbohydrates, terpenoids, saponins, alkaloids, sterols and tannins. The antimicrobial screening was done using disc diffusion method with disc potency of 60µg/disc, 30µg/disc and 15µg/disc respectively and two groups of test organisms (bacteria and fungi) were used. The ethyl acetate and ethanolic extract were found to be effective on both groups of test organisms while the hexane extract did not show any activity on all the test organisms used. Concentrations of the plant extracts required for 50% inhibition of DPPH radical scavenging effect (IC50) were recorded as 8.67, 0.64, 0.31 and 0.14 mg/ml for the hexane fraction, ethyl acetate fraction, ethanol fraction and vitamin C respectively.   Keywords: Antimicrobial, antioxidant, Ensete gilletii, phytochemical, proximate.